2023
DOI: 10.3390/vaccines11050911
|View full text |Cite
|
Sign up to set email alerts
|

Role of Healthcare Professionals and Sociodemographic Characteristics in COVID-19 Vaccination Acceptance among Uro-Oncology Patients: A Cross-Sectional Observational Study

Abstract: At the time when mass COVID-19 vaccination began, providing appropriate vaccination advice to uro-oncology patients became a challenge. This was a single-center cross-sectional observational study aimed to investigate the rate of COVID-19 vaccination among uro-oncology patients receiving systemic therapy for metastatic renal cell carcinoma and metastatic castration-resistant prostate cancer. Furthermore, we aimed to assess patients’ attitudes and identify factors influencing their decision to vaccinate against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Furthermore, men are more likely to experience more severe COVID-19 infection outcomes and morphologies, according to a meta-analysis by Booth et al, which may help to explain our results. Nonetheless, contrary to what we found, other research has indicated that women are more likely to accept vaccinations [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, men are more likely to experience more severe COVID-19 infection outcomes and morphologies, according to a meta-analysis by Booth et al, which may help to explain our results. Nonetheless, contrary to what we found, other research has indicated that women are more likely to accept vaccinations [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, compared to patients who lived alone or with multiple household members, those who shared a residence had the highest vaccination rate. Additionally, their results demonstrated that patients were more likely to get vaccinated themselves if they indicated that a family member's influence had a significant role in their decision to finish immunization and if they had family members who had received the COVID-19 vaccine [17]. The authors argue that the high frequency of conspiracy theories regarding COVID-19, which was purposefully introduced into the world to aid in the development of vaccines against it, may be the cause of these disparities in vaccination willingness among various nations.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers (HPs) and parents are the two pillars of vaccination programs highlighted by the literature. The role of HPs in facilitating vaccination is vital [ 17 , 18 , 19 , 20 ], and, although they can differ in terms of stance toward vaccination [ 21 ], the majority have a strong positive consensus [ 22 ].…”
Section: Introductionmentioning
confidence: 99%